The saddle angle and its relationship with different sagittal skeletal patterns for Iraqi population - Lamis Khidher Mohammed; Issam Merzah Abdullah; Kasem Ahmed Abeas; Arkan M Al Azzawi (Medical Journal of Babylon, 2023)
Background: The cranial base has a substantial role in determining how the maxilla and mandible are related to each other and its growth influences the maxillo-mandibular growth. Aim: The main aim of this study was to evaluate and assess the relationship of the saddle angle (NSAr) with different patterns of the sagittal interarch skeletal relationship for the Iraqi population and detect the effect of gender on it. Materials and Methods: The samples included 125 true lateral cephalometric radiographs for Iraqi patients of both genders (male and female) between the age of 18–25 years obtained from the clinic’s archives of the Orthodontic Department at the Dentistry Teaching Hospital of the Faculty of Dentistry, Baghdad University, Iraq, who was looking for orthodontic therapy. The samples were divided according to the value of ANB angle into skeletal Cl I (33 females and 14 males), skeletal Cl II (27 females, 14 males), and skeletal Cl III (17 females and 20 males) groups, then the saddle angle were digitized and recorded using AutoCAD 2012 computer program, the data then analyzed by SPSS version 24 (2016) computerized statistical analysis. Results: The results clarified that the mean value of saddle angle was smaller in the skeletal Cl III group for both genders, with females showed the smallest value with no significant difference, and the larger value of saddle angle was in the skeletal Cl II group for both genders with females showed the largest value with no significant difference. Conclusion: The sagittal skeletal relationship tends to alter from skeletal Cl III to Cl II with progressive flattening of the cranial base and vice-versa. The effect of gender on saddle angle was more than that of sagittal skeletal classes.